2020
DOI: 10.1016/j.conbuildmat.2020.118030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of recycled aggregate concrete modified by nano-particles

Abstract: In this study, different nano-particles were used to modify recycled aggregates concrete (RAC) containing recycled clay brick aggregates (RCBAs) to improve the RAC properties. Two stages of experimental works were performed. In the first stage, various nano-particle mixtures produced by different mixing methods, i.e. the use of surfactant and ultrasonication, were examined by optical microscope to evaluate the dispersion of the nano-particles in water liquid. The nano-particles modified cement mortar specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(22 citation statements)
references
References 49 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…Some consistent research conclusions were reached that the recycled concrete exhibited lower strength than ordinary concrete [ 4 ], and recycled aggregates caused more significant shrinkage and water absorption in the resulting concrete [ 1 , 6 ]. It is worthy to note that the adopted recycled aggregates were resulted from broad sources, e.g., demolished concrete [ 7 , 8 , 9 ], bricks [ 10 , 11 , 12 , 13 , 14 ], and ceramic tile [ 15 ], and the uncertainty surrounding the sources of recycle aggregates could cause variability in the resulting concrete. Some existing scholarly works concluded that: (1) the compressive strength of recycled concrete was 37% or more lower than that of ordinary concrete, and the adhered mortar had an adverse influence on the concrete’s strength [ 16 ], (2) the replacement ratios of recycled coarse aggregates within 25% or recycled fine aggregates within 30% rarely exhibited inferior effects on the strength and durability of the resulting concrete [ 17 ], (3) the recycled concrete failed in shear mode with a larger peak strain, but the ductility of recycled concrete was decreased compared with ordinary concrete [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some consistent research conclusions were reached that the recycled concrete exhibited lower strength than ordinary concrete [ 4 ], and recycled aggregates caused more significant shrinkage and water absorption in the resulting concrete [ 1 , 6 ]. It is worthy to note that the adopted recycled aggregates were resulted from broad sources, e.g., demolished concrete [ 7 , 8 , 9 ], bricks [ 10 , 11 , 12 , 13 , 14 ], and ceramic tile [ 15 ], and the uncertainty surrounding the sources of recycle aggregates could cause variability in the resulting concrete. Some existing scholarly works concluded that: (1) the compressive strength of recycled concrete was 37% or more lower than that of ordinary concrete, and the adhered mortar had an adverse influence on the concrete’s strength [ 16 ], (2) the replacement ratios of recycled coarse aggregates within 25% or recycled fine aggregates within 30% rarely exhibited inferior effects on the strength and durability of the resulting concrete [ 17 ], (3) the recycled concrete failed in shear mode with a larger peak strain, but the ductility of recycled concrete was decreased compared with ordinary concrete [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A common method for obtaining high-strength concretes is the addition of carbon nanotubes (CNTs) or multilevel carbon nanotubes (MWCNTs) [ 22 , 23 , 24 , 25 , 26 ]. CNTs modify the failure process in the cement matrix where microcracks are initiated with “significantly improved fracture energy resulting in improved global mechanical properties and a nanosized interfacial transition zone is found which determines the failure of the nanocomposite system” [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the usage of RAC in practical construction usually requires some enhancement treatments regarding the microstructure of recycled aggregates including the heat treatment [ 9 ], ultrasonic cleaning [ 10 ], carbon dioxide injection [ 11 ], etc. [ 12 , 13 , 14 ]. On the other hand, RAC in some forms of composite structures shows more reliable and uniform mechanical properties and is supposed to overcome the aforementioned application barriers.…”
Section: Introductionmentioning
confidence: 99%